The Role of Social Support and Life Satisfaction on Academic Burnout in Dental Students of Zahedan University of Medical Sciences in 2023 - hamideh kadeh; Paria Moazeni (Mashhad University of Medical Sciences, 2024)
Background: Academic burnout in students is characterized by feeling tired of doing homework, having a pessimistic attitude towards education and academic courses, and a sence of academic incompetence. The present study aimed to investigate the role of social support and life satisfaction in academic burnout of dental students in Zahedan University of Medical Sciences.Materials and Methods: In this cross-sectional study, 162 dental students attending Zahedan University of Medical Sciences entered the study. The sample was obtained using a census-based sampling method and according to the inclusion criteria. Data were collected using Breso Academic Burnout Questionnaire, Diener Life Satisfaction Questionnaire and Zimet Perceived Social Support Multidimensional Scale Questionnaire. Data were subjected to statistical analysis using SPSS version 18 and was analyzed using the independent T-test, ANOVA and linear regression analysis.                           Results: According to the results, 65.4% (106) of students were at high levels of academic burnout. The scores of social support (4.53± 0.84) and life satisfaction (13.38± 4.07) were also in the moderate range in most students. The analysis of the data did not show any significant differences in average social support, life satisfaction and academic burnout with gender and academic term (p>0.05), and the results of the regression analysis showed that life satisfaction and social support had an inverse and significant effect (β= - 0.156 and β= - 0.290) on academic burnout.Conclusion: According to the findings of the current study, most dental students had a high level of academic burnout and social support and life satisfaction of most students were not at a desirable level. Since social support and life satisfaction have had a significant and inverse impact on academic burnout, ameliorating these two components can make a significant contribution to reducing the rate of academic burnout among dental students.